Enhanced CASSI Snapshot Imager Using Dual Prism Dispersion - Ding, Mengjia (Cranfield University, 2017)
Poster and 3MT presentation at the 2016 Defence and Security Doctoral Symposium. Snapshot Multispectral Imaging has been a highly-efficient technique for remote sensing application in great contrast to the conventional scanning system on the aspect of military target detection, agricultural monitoring and medical examination. Among many snapshot multispectral imagers, Coded Aperture Snapshot Spectral Imager(CASSI) has been introduced for a decade with the exploitation of a simple combination of coded aperture mask and dispersive element to acquire spatial and spectral data simultaneously. My work is to use an adjustable dual-prism structure rather than the conventional single prism/double amici prism to extend the image reconstruction ability of the current CASSI system in terms of tuneable spectral channels. The simulations are carried out by ray tracing software TracePro and the performance of the system is assessed by Matlab.
Keywords: 'DSDS16 poster'; 'DSDS16 3MT'; 'DSDS16'; 'Snapshot imaging'; 'Multispectral imaging'; 'Optical system design'; 'Photonics and Electro-Optical Engineering (excl. Communications)'